Women Representation in Nepalese Local Election 2017: Issues and Challenges - Manandhar, Sanju (Journal of Political Science, 2021)
Democracy is for power and justice. Women's participation in politics is for achieving these twin goals. The main objective of this study is to reviews the women representation at Nepalese local in political domain. The essential data and information are collected from secondary sources. Reports, information, facts, figures, policies, acts and program published by Nepal Election Commission-2017 and other related sources reports are basically used in this paper. One of the key factors to ensure higher and meaningful participation of women in politics is these favorable (reservation) electoral provisions. The 2017 local elections were significant in advancing female political representation in Nepal. However, what has been achieved so far is not enough and continued concentrated action is essential. There are more issues and challenges to be resolve for fair and meaningful political participation of women. The women's representation in politics should not be just a numeric representation. It should rise in the societal awareness for women and build capacity of female leaders and ultimately helps in the overall development of the country.